Testing the utility of the first step of system evaluation theory in creating a system map of care for cardiac amyloidosis early detection: A case study - Sherry L. Ball; Alexis Koskan; Jenice Guzman; Sandesh Dev (PLoS ONE, 2026)
Background Heart failure is a clinical syndrome resulting from numerous pathological conditions. One cause of heart failure, transthyretin cardiac amyloidosis, presents insidiously with common and seemingly unrelated symptoms. New treatments for cardiac amyloidosis are available that extend and improve life. However, providers are not testing patients for transthyretin cardiac amyloidosis. We took a systems science approach to explore the system of care for transthyretin cardiac amyloidosis testing by depicting the healthcare system from patient presentation to treatment. Our goal was to define an ideal healthcare system to improve the uptake of testing protocols and enhance patient outcomes. Methods We assembled clinicians, researchers, and patients to participate in a co-design workshop using the first step of System Evaluation Theory to define an ideal testing and diagnostic protocol using transthyretin cardiac amyloidosis as a case study. We tasked workshop attendees with defining the patient and clinician journey from symptom presentation to diagnosis. We generated a system map using a qualitative matrix analysis of a transcript of the workshop discussion. Results The matrix analysis organized input from all stakeholders, allowing for the creation of a system map that reveals the complexity of the transthyretin cardiac amyloidosis testing process and potential implementation strategies to improve the efficiency and effectiveness of the system. This methodology successfully yielded generalizable elements of a testing protocol and testable strategies to facilitate the implementation of a protocol adapted to fit local site needs. Conclusions The substeps outlined within System Evaluation Theory Step 1 helped identify an ideal system for testing and diagnosing transthyretin cardiac amyloidosis care that could be applied to specific settings to identify, improve, and implement protocols for other complex diseases.